Food Security a Top Priority - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Mr Mignannou Fandy, CJSMR, Cotonou, Benin: 'l have an observation which I would like to see inscribed in SPORE. It isthis: who among men can survive without the fruit of the soil? I do not understand why man pays so little attention to soil. So...